PENGGUNAAN SARANA NON PENAL OLEH PUSAT PELAYANAN TERPADU PEMBERDAYAAN PEREMPUAN DAN ANAK PROVINSI RIAU DALAM PENCEGAHAN TINDAK PIDANA PERDAGANGAN ANAK DI BAWAH UMUR BERDASARKAN UNDANG-UNDANG NOMOR 35 TAHUN 2014 ATAS PERUBAHAN UNDANG-UNDANG NOMOR 23 TAHUN 2002 TENTANG PERLINDUNGAN ANAK - Dwita Puspita Sari; Erdianto '; Dessy Artina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Trafficking in persons, especially the trafficking of minors, has grown and globalized, its handling has received less attention in the community due to lack of socialization to the public. In Riau Province, a Government agency is formed, namely Integrated Service Center (P2TP2A). This writing in the background by the rise of various trafficking modes, especially underage girls, ranging from promised jobs, abduction of victims, debt bondage, and fraud. In addition victims are trafficked not only for the purpose of prostitution or other forms of sexual exploitation, but also include other exploits, such as forced labor or forced service, slavery or similar practices of slavery. The purpose of this essay is to know, to analyze the role of P2TP2A institution of Riau Province in preventing the crime of trafficking of underage child as commercial sex worker, to study and to know the obstacles faced by P2TP2A Institution of Riau Province and it’s effort in overcoming The crime of trafficking of minors.This type of research can be classified in the type of research Sociological Juridical, because in this study the authors directly conduct research on the location or place studied to provide a clear picture of the problem under study. This research was conducted at the Center for Integrated Service of Women and Children Empowerment (P2TP2A) Riau Province, while the population and the sample which is whole party related to the problem studied in this research, the data source used is primary data, secondary data and tertiary data, data collection techniques in this study was conducted by interview and literature review.From the research results, there are three things that can be concluded. Firstly, in addressing the problem of child trafficking which increases every year, P2TP2A Riau Province do prevention in the form of non penal effort that is disseminating to RT / RW in some Regency / City in Riau Province region. Second, the obstacles was faced by Riau Province P2TP2A institution in doing prevention (non penal) divided into internal and external obstacles. Third, the efforts made by P2TP2A Riau Province in overcoming the internal and external obstacles is by coordinating with the government and the community. The suggestions that can be given in this writing are as follows, First, the Government of Riau Province is expected to be more sensitive to the performance of P2TP2A in order to perform effectively, and support P2TP2A facilities and infrastructure. Secondly, in preventing and combating the trafficking of underage child trafficking, P2TP2A Riau Province is expected to continue to make preventive efforts such as socialization, supervision, and others.